8-weeks aerobic exercise ameliorates cognitive deficit and mitigates ferroptosis triggered by iron overload in the prefrontal cortex of APPSwe/PSEN1dE9 mice through Xc−/GPx4 pathway - Li, Chaoyang; Cui, Kaiyin; Zhu, Xinyuan; Wang, Shufan; Yang, Qing; Fang, Guoliang (Frontiers in Neuroscience, 2024)
BackgroundAlzheimer’s disease (AD) is a degenerative disorder of the central nervous system characterized by notable pathological features such as neurofibrillary tangles and amyloid beta deposition. Additionally, the significant iron accumulation in the brain is another important pathological hallmark of AD. Exercise can play a positive role in ameliorating AD, but the mechanism is unclear. The purpose of the study is to explore the effect of regular aerobic exercise iron homeostasis and lipid antioxidant pathway regarding ferroptosis in the prefrontal cortex (PFC) of APPSwe/PSEN1dE9 (APP/PS1) mice.MethodsEighty 6-month-old C57BL/6 J and APP/PS1 mice were divided equally into 8-weeks aerobic exercise groups and sedentary groups. Subsequently, Y-maze, Morris water maze test, iron ion detection by probe, Western Blot, ELISA, RT-qPCR, HE, Nissle, Prussian Blue, IHC, IF, and FJ-C staining experiments were conducted to quantitatively assess the behavioral performance, iron levels, iron-metabolism-related proteins, lipid antioxidant-related proteins and morphology in each group of mice.ResultsIn APP/PS1 mice, the increase in heme input proteins and heme oxygenase lead to the elevated levels of free iron in the PFC. The decrease in ferritin content by ferritin autophagy fails to meet the storage needs for excess free iron within the nerve cells. Ultimately, the increase of free ferrous iron triggers the Fenton reaction, may lead to ferroptosis and resulting in cognitive impairment in APP/PS1 mice. However, 8-weeks aerobic exercise induce upregulation of the Xc−/GPx4 pathway, which can reverse the lipid peroxidation process, thereby inhibiting ferroptosis in APP/PS1 mice.Conclusion8 weeks aerobic exercise can improve learning and memory abilities in AD, upregulate GPx4/Xc− pathway in PFC to reduce ferroptosis induced by AD.